اللغة العربية قبل الإسلام - Nur Hidayat (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2018)
Language is a set of words used by a group of people to express or reveal a purpose. Arabic is one of the Sam languages, Arab nation is a kind of Sam  nations (identical to sam ibn nuh). As we all know that the Arabic language is not only used by the Arab nation, but also used in many nations of the world. Before the arrival of the Islamic religion in the Arab nation, the Arab nation lives in the Jahiliyyah. Arabic civilization before Islam in the social field has a bad social order, but in the field of arts and language is highly advanced. The Arabic language since its oldest era has been divided  into many dialects that differ from each other in many aspects of Phonology, Semantic, Sintax, and Vocabulary